Evaluasi Tingkat Kepuasan Pengguna Aplikasi Unmer Malang Digital Library Menggunakan Metode EUCS - Aldiansyah, Muhammad Yusuf; Jatmiko, Andriyan Rizki (J-INTECH (Journal of Information and Technology), 2024)
The Unmer Malang Digital Library application, an online platform established on December 14, 2023, has not yet been reviewed from a user satisfaction perspective since its inception. This study aims to evaluate user satisfaction with the application and test related hypotheses. Utilizing the End User Computing Satisfaction method and the Accidental Sampling technique for data collection, the results indicate that users are generally satisfied with the platform. Scores for various variables were: content at 3.89, accuracy at 4.15, layout averaging 4.06, ease of use at 4.11, and timeliness averaging 4. The study's hypothesis suggests that accuracy, format, and timeliness significantly affect user satisfaction, whereas content and ease of use do not have a notable impact.